1959
DOI: 10.1180/minmag.1959.032.247.04
|View full text |Cite
|
Sign up to set email alerts
|

A dickite with an elongated crystal habit and its dehydroxylation

Abstract: Summary. Dickite from a new occurrence at Barkly East, Cape Province, is described and compared with a previously unreported dickitc from Postmashurg and a dickite from Ouray, Colorado. The Barkly East dickite crystals are elongated in the direction of the a-axis ; the ratio of length to width of crystals varies from 3:1 to 16:1. Optical, electron microscopic, X-ray, and thermal data and a chemical analysis are given. The thermogram of the fraction smaller than 2 g e.s.d. 1 is characterized by a single peak at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Preparation of this material in a one-stage synthesis also follows the procedure defined for CdSe. 4. The reaction Zn-Se also closely resembles the Cd-Se reaction, with the notable difference that a single stage complete powder synthesis can be effected at rates as high as 3°/min.…”
Section: Methodsmentioning
confidence: 86%
“…Preparation of this material in a one-stage synthesis also follows the procedure defined for CdSe. 4. The reaction Zn-Se also closely resembles the Cd-Se reaction, with the notable difference that a single stage complete powder synthesis can be effected at rates as high as 3°/min.…”
Section: Methodsmentioning
confidence: 86%
“…Additional data closely related to the hypogene enargite metallization need further study. We believe that the genesis of the elongate dickite crystals in the CKS and NSC areas has a hydrothermal origin as postulated by Schmidt and Heckroodt (1959).…”
Section: Relationship Of Genesis To Crystal Morphologymentioning
confidence: 84%
“…Dickite crystals are either of hexagonal form or are platelets elongated parallel to the a axis (Figure 6b). This elongated habit is common in hydrothermal dickite (Schmidt and Heckroodt, 1959). …”
Section: Chen Wang and Yangmentioning
confidence: 99%
“…(2) Dickite from Ebara, Hyogo Prefecture, Japan (Ueno, 1964). (3) Dickite from Barkly East, Cape Province, South Africa (Schmidt and Heckroodt, 1959). (Table 2) reveals that the sample contains small amounts of Li ions.…”
Section: Mineralogy Of Clays In the H-type Alteration Aureolementioning
confidence: 99%
“…Smithson and Brown (1957) studied the dehydroxylation of a well-ordered, pure dickite from Anglesey, Wales, and concluded that the double endotherms they found must be due to the dickite. Schmidt and Heckroodt (1959) studied the dehydroxylation of various size fractions of a dickite from Barkly East. They observed that the 6.3-20 um size fractions showed double endothermic peaks, the higher temperature peak of which was missing for the < 2-/~m fractions.…”
Section: Mineralogy Of Clays In the H-type Alteration Aureolementioning
confidence: 99%